2003
DOI: 10.1002/pi.1157
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic synthesis and characterization of an alternating copolymer from carbon dioxide and propylene oxide using zinc pimelate

Abstract: New zinc pimelate catalysts used for copolymerization of carbon dioxide and propylene oxide have been synthesized in high yield by a magnetic stirring method. The regular molecular structure of the zinc pimelate was confirmed by Fourier‐transform infrared spectroscopy and wide‐angle X‐ray diffraction techniques. Accordingly, poly(propylene carbonate) (PPC) can be synthesized from carbon dioxide and propylene oxide using these zinc pimelate catalysts. High catalytic efficiency (95.2 gram polymer per gram cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…[38] Zinc carboxylate copolymerization catalysts prepared from salts like zinc oxide, zinc carbonates and/or hydroxides and carboxylic acids are more convenient to handle and utilize cheaper starting materials. A preferred catalyst is prepared from glutaric acid, [5,39,40] but also zinc compounds prepared from adipinic, [41] pimelic, [42] phthalic, [43] or mixtures of carboxylic acids [44] show activity. [45] This type of catalyst is preferentially used for the commercial preparation of aliphatic polycarbonates starting from EO or mono-substituted oxiranes, as they give high-molecular-weight polycarbonates with a high carbonate content and little formation of cyclic byproducts.…”
mentioning
confidence: 99%
“…[38] Zinc carboxylate copolymerization catalysts prepared from salts like zinc oxide, zinc carbonates and/or hydroxides and carboxylic acids are more convenient to handle and utilize cheaper starting materials. A preferred catalyst is prepared from glutaric acid, [5,39,40] but also zinc compounds prepared from adipinic, [41] pimelic, [42] phthalic, [43] or mixtures of carboxylic acids [44] show activity. [45] This type of catalyst is preferentially used for the commercial preparation of aliphatic polycarbonates starting from EO or mono-substituted oxiranes, as they give high-molecular-weight polycarbonates with a high carbonate content and little formation of cyclic byproducts.…”
mentioning
confidence: 99%
“…The catalytic synthesis of PPC has been extensively studied and reported [3][4][5][6][7] . We have demonstrated that supported zinc glutarate can be used as the catalyst of the synthesis of PPC at large scale [4,8] . Therefore, the application studies become more and more important.…”
Section: Introductionmentioning
confidence: 98%
“…Since the pioneering work of Inoue in 1969 [2], the synthesis of aliphatic polycarbonates from carbon dioxide and epoxides has attracted longstanding interest as potential method of using CO 2 [3,4]. Aliphatic polycarbonate represents one family of biodegradable materials used for biomedical applications, such as drug carriers and implant materials because of their good biocompatibility, low toxicity, and biodegradability [5].…”
Section: Introductionmentioning
confidence: 99%